Influence of microjets on flow development at supersonic mach numbers with sudden expansion - Delvi, Hamza Afser; Ridwan, R; Muneer, Rayid; Faheem, Mohammed; Khan, Sher Afghan (IOP Publishing, 2021)
This paper presents the control of suddenly expanded flow using four microjets at the base recirculation zone for a diameter ratio of 1.8. Eight Mach numbers are considered for investigations from 1.25 to 3. The NPRs for which the tests were conducted were from 3 to 11. The duct length considered was L = 10D to 1D. This article has shown only selected results when there is significant variation in the duct's flow field; only those cases are considered. For most of the cases, the flow remains identical with and without control. For Mach M = 1.25 to 2.5, the control results in a decline in the duct's pressure when the flow is within the reattachment length. Later there is a progressive rise in the duct pressure. However, the trend is reversed at Mach M 3.0. The least duct stretches necessary intended for the stream to continue to relate to the pipe are L = 1D, 2D, and 3D for the study's Mach number.